Moldando a nova Pátria: o ensino primário na construção do patriotismo e civismo em Angatuba/SP (1930-1945) - Rocha, Diego Tadeu de Oliveira (Universidade Federal de São Carlos, 2022)
This dissertation has as its theme the development of the civic-patriotic formation that occurred in the city of Angatuba/SP during the first government of Getúlio Vargas (1930-1945), from the pedagogical instruments used in primary education. The problem that guided the investigation questioned how the mechanisms of reproduction of patriotism, civism, moralism and nationalism were developed in primary education with the use of the "authoritarian pedagogy" focused on the formation of the conscience of the "new Brazilian citizen", with the objective imposed on education by the Vargas government line of thought, making the educational process an important instrument for the consolidation of political ideals. To do so, in the context of the History of Education, the methodology of the plural typological pluralism of documents was used in face of the bibliographical and documental research, as well as the qualitative research, consulting dialectically the primary sources preserved in the locality, such as the newspaper A Folha de Angatuba, the primers and textbooks, besides the collection of orality. The research aimed, therefore, to understand the organization of the pedagogical process in primary education as an instrument to form the feeling of belonging and love for the homeland in the future Brazilian citizens.

Esta disertación tiene como tema el desarrollo de la formación cívico-patriótica ocurrida en la ciudad de Angatuba/SP durante el primer gobierno de Getúlio Vargas (1930-1945), a partir de los instrumentos pedagógicos utilizados en la educación primaria. El problema que orientó la investigación fue cuestionar cómo se desarrollaron los mecanismos de reproducción del patriotismo, el civismo, el moralismo y el nacionalismo en la instrucción del nivel primario con el uso de la "pedagogía autoritaria" centrada en la formación de la conciencia del "nuevo ciudadano brasileño", siendo el objetivo impuesto a la educación por la línea de pensamiento del gobierno de Vargas, haciendo del proceso educativo un importante instrumento de consolidación de los ideales políticos. Para ello, en el contexto de la Historia de la Educación, se utilizó la metodología del pluralismo tipológico de documentos frente a la investigación bibliográfica y documental, así como la investigación cualitativa, consultando dialécticamente las fuentes primarias conservadas en la localidad, como el periódico A Folha de Angatuba, las cartillas y libros de texto, además de la colección de la oralidad. Por lo tanto, la investigación tuvo como objetivo comprender la organización del proceso pedagógico en la educación primaria como instrumento formativo del sentido de pertenencia y amor a la patria en los futuros ciudadanos brasileños.

Cette thèse a pour thème le développement de la formation civique-patriotique qui a eu lieu dans la ville d'Angatuba/SP pendant le premier gouvernement de Getúlio Vargas (1930-1945), à partir des instruments pédagogiques utilisés dans l'enseignement primaire. Le problème qui a guidé l'enquête a été de savoir comment les mécanismes de reproduction du patriotisme, du civisme, du moralisme et du nationalisme ont été développés dans l'enseignement primaire avec l'utilisation de la "pédagogie autoritaire" axée sur la formation de la conscience du "nouveau citoyen brésilien", étant l'objectif imposé à l'éducation par la ligne de pensée du gouvernement Vargas, faisant du processus éducatif un instrument important de consolidation des idéaux politiques. Pour cela, dans le contexte de l'Histoire de l'Éducation, on a utilisé la méthodologie du pluralisme typologique de documents face à la recherche bibliographique et documentaire, ainsi que la recherche qualitative, en consultant dialectiquement les sources primaires conservées dans la localité, comme le journal A Folha de Angatuba, les abécédaires et les manuels, outre la collection de l'oralité. Par conséquent, la recherche visait à comprendre l'organisation du processus pédagogique dans l'enseignement primaire en tant qu'instrument formateur du sentiment d'appartenance et de l'amour de la patrie chez les futurs citoyens brésiliens.

Questa dissertazione ha come tema lo sviluppo della formazione civico-patriottica avvenuta nella città di Angatuba/SP durante il primo governo di Getúlio Vargas (1930-1945), a partire dagli strumenti pedagogici utilizzati nell'educazione primaria. Il problema che ha guidato l'indagine si è interrogato su come i meccanismi di riproduzione del patriottismo, civismo, moralismo e nazionalismo sono stati sviluppati nell'istruzione primaria con l'uso della "pedagogia autoritaria" incentrata sulla formazione della coscienza del "nuovo cittadino brasiliano", essendo l'obiettivo imposto all'educazione dalla linea di pensiero del governo Vargas, rendendo il processo educativo un importante strumento di consolidamento degli ideali politici. Per questo, nel contesto della Storia dell'Educazione, è stata utilizzata la metodologia del pluralismo tipologico dei documenti di fronte alla ricerca bibliografica e documentale, così come la ricerca qualitativa, consultando dialetticamente le fonti primarie conservate nella località, come il giornale A Folha de Angatuba, i primer e i libri di testo, oltre alla raccolta dell'oralità. Pertanto, la ricerca mirava a comprendere l'organizzazione del processo pedagogico nell'educazione primaria come strumento formativo del senso di appartenenza e dell'amore per la patria nei futuri cittadini brasiliani.
Molding the new Homeland: primary education in the construction of patriotism and civism in Angatuba/SP (1930-1945)
Formando la nueva patria: la educación primaria en la construcción del patriotismo y el civismo en Angatuba/SP (1930-1945)
Keywords: Educação primária; Civismo; Patriotismo; Governo Vargas (1930-1945); Comemorações cívicas; Angatuba/SP; Educação patriótica; Primary education; Civism; Patriotism; Vargas Government (1930-1945); Civic commemorations; Patriotic education; Educación primaria; Gobierno de Vargas (1930-1945); Conmemoraciones cívicas; Educación patriótica; Enseignement primaire; Civisme; Patriotisme; Gouvernement Vargas (1930-1945); Commémorations civiques; Éducation patriotique; Educazione primaria; Patriottismo; Commemorazioni civiche; Educazione patriottica; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::HISTORIA::HISTORIA DO BRASIL; CIENCIAS HUMANAS::HISTORIA::TEORIA E FILOSOFIA DA HISTORIA